Modeling Risk Factors of Dysmenorrhea in Adolescent - Ardianto, Efri Tri; Dwi Elisanti, Alinea (Universitas STRADA Indonesia, 2019)
Dysmenorrhoea is more widely experienced by adolescents due to stress, lack of rest, lack of exercise and balanced nutrition. Some impact on teenagers in schools is declining spirit of learning, impaired concentration, there are up to leave the activity. In Indonesia, the incidence of dysmenorrhoea in teenagers consists of 54.89%. This study wants to modeling the risk factor of dysmenorrhoea in an adolescent. This research uses the analytical method by using the cross-sectional study design. As many as 57 student populations with a large sampling of 51 adolescent girls at SMAN 1 Menganti. Simple random sampling was used as sampling techniques. With research tools such as hemoglobin examination, measurement of body weight and height using digital and microtoise scales, questionnaire to identify knowledge, physical activity, anemia and Mass Body Index in adolescents girls. The result obtained the adolescent who has less physical activity will 7,441 times greater to experience dysmenorrhea than good physical activity, the adolescent who has less knowledge 0.241 times more likely to experience dysmenorrhea than good knowledge and the adolescent who has anemic disease was 20,123 times more likely to experience dysmenorrhea than has not anemia disease. Healthy living behavior, adequate vitamin intake, reduced mind burden, adequate rest and regular exercise need to continue to be the main message in providing health education to adolescents. Included in it is a message to avoid an unbalanced diet